2006
DOI: 10.1002/chin.200637102
|View full text |Cite
|
Sign up to set email alerts
|

1,3‐Dipolar Cycloaddition of Difluoro‐Substituted Azomethine Ylides. Synthesis and Transformations of 2‐Fluoro‐4,5‐dihydropyrroles.

Abstract: Pyrrole derivatives R 0120 1,3-Dipolar Cycloaddition of Difluoro-Substituted Azomethine Ylides. Synthesis and Transformations of 2-Fluoro-4,5-dihydropyrroles. -Reactions of difluorocarbene with N-substituted ketone imines in the presence of fumaronitrile, maleonitrile or maleate provides a convenient access to 2-fluoro-4,5-dihydropyrrole derivatives. The reactions involve the intermediate formation of difluoro-substituted azomethine ylides and their subsequent cycloaddition. -(NOVIKOV, M. S.; KHLEBNIKOV, A. F.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The classical approach to prepare the structures is the electrochemical oxidative fluorination of organic compounds such as oxazolidines, where unselective fluorination proceeds, leading to perfluorinated products 24,25 . However, despite the substantial progress in methods using difluorocarbene, there have been only two reports on the preparation of isolable α,α-difluorinated N-heterocycles via multicomponent cycloadditions with difluorocarbene; these reactions require a stoichiometric amount of toxic lead for the reduction of dibromodifluoromethane to generate difluorocarbene, and the substrate scope is quite narrow, with only five examples using specific ketimines, ketones and fumaronitrile under ultrasonic irradiation 36,37 . To develop a practical multicomponent reaction with a broad substrate scope, we chose reaction conditions using less toxic reagents for the generation of difluorocarbene and explored two substrates that were suitable for the predicted reaction mode shown in Fig.…”
Section: In Silico Reaction Screening With Difluorocarbene For N-difl...mentioning
confidence: 99%
See 1 more Smart Citation
“…The classical approach to prepare the structures is the electrochemical oxidative fluorination of organic compounds such as oxazolidines, where unselective fluorination proceeds, leading to perfluorinated products 24,25 . However, despite the substantial progress in methods using difluorocarbene, there have been only two reports on the preparation of isolable α,α-difluorinated N-heterocycles via multicomponent cycloadditions with difluorocarbene; these reactions require a stoichiometric amount of toxic lead for the reduction of dibromodifluoromethane to generate difluorocarbene, and the substrate scope is quite narrow, with only five examples using specific ketimines, ketones and fumaronitrile under ultrasonic irradiation 36,37 . To develop a practical multicomponent reaction with a broad substrate scope, we chose reaction conditions using less toxic reagents for the generation of difluorocarbene and explored two substrates that were suitable for the predicted reaction mode shown in Fig.…”
Section: In Silico Reaction Screening With Difluorocarbene For N-difl...mentioning
confidence: 99%
“…The reaction of two methanimines and difluorocarbene gave fluorinated cyclic product A2 in the simulations. After an investigation to determine suitable reactants and their protecting groups, we found that N-Boc-protected imines are suitable for the proposed cycloaddition to provide the difluorinated products (36)(37)(38)(39); the major components were confirmed to be endo-isomers as well as the products from aldehydes or ketones via NOE analysis of 39. The multicomponent cycloaddition of methanimine, difluorocarbene and ethylene as an alkene source (which was predicted to generate cyclic product A3 in the AFIR search) was realized using alkenes such as acrylonitrile or methyl methacrylate derivatives, affording dihydroindolizine products (40-48) bearing quaternary carbon stereocentres.…”
Section: Scope Of the N-difluoroalkylative Dearomative Cycloadditionmentioning
confidence: 99%